2018
DOI: 10.3389/feart.2018.00063
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of Increasing Flash Flood Frequency in the Densely Urbanized Coastline of the Campi Flegrei Volcanic Area, Italy

Abstract: Climate change is affecting the frequency and severity of extreme meteorological and geo-hydrological events hitting the coastal zone of the Campi Flegrei volcanic district (southern Italy), which is prone to a wide spectrum of natural hazards, including volcanism, earthquakes, ground deformation, flash floods, landslides, and coastal erosion. This study documents the trend of flash floods affecting the town of Pozzuoli, located along the coastline of the Campi Flegrei volcanic area, during the 1970-2014 time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 44 publications
1
26
0
Order By: Relevance
“…For urban flash flooding arising from catchments draining the hinterland of Genoa (Liguria, Italy), Faccini et al (2018) stressed the importance of rainfall intensities over periods of 1-3 h, while Papagiannaki et al (2015) in Greece showed that urban flash flooding was probable for I 10 > 22.8 mm h −1 (or I 60 > 9.6 mm h −1 ). For Italy, Esposito et al (2018) reported flash flood thresholds of I 10 > 54 mm h −1 or I 60 > 30 mm h −1 . In catchments in SW Germany, Ruiz-Villanueva et al (2012) showed that I 30 offered less explanatory power than I 60 for catchments > 10 km 2 , owing to their longer response time (greater smoothing of the hydrologic response).…”
Section: What Evidence Points To the Significance Of Short-lived Intementioning
confidence: 99%
See 1 more Smart Citation
“…For urban flash flooding arising from catchments draining the hinterland of Genoa (Liguria, Italy), Faccini et al (2018) stressed the importance of rainfall intensities over periods of 1-3 h, while Papagiannaki et al (2015) in Greece showed that urban flash flooding was probable for I 10 > 22.8 mm h −1 (or I 60 > 9.6 mm h −1 ). For Italy, Esposito et al (2018) reported flash flood thresholds of I 10 > 54 mm h −1 or I 60 > 30 mm h −1 . In catchments in SW Germany, Ruiz-Villanueva et al (2012) showed that I 30 offered less explanatory power than I 60 for catchments > 10 km 2 , owing to their longer response time (greater smoothing of the hydrologic response).…”
Section: What Evidence Points To the Significance Of Short-lived Intementioning
confidence: 99%
“…Simultaneous changes in global and regional hydroclimates, related to global warming and shifts in the nature of the hydrologic cycle, may result in increased frequency and erosivity of rainfall events (Hatfield et al, 2013), as well as related ecosystem changes including in floristics, plant architecture, and soil moisture content. At the same time, growth in urban areas and populations, and the associated impervious urban land surfaces, appears to be resulting in increased risk of urban flash flooding and associated sediment transport, especially in peri-urban areas (Esposito et al, 2018), though this may be partially offset by the growing adoption of "sponge city" and similar approaches to building more absorbent cities Dong et al, 2018). Archer and Fowler (2018) have illustrated the effects of short-term "intensity bursts" in UK flooding, emphasising that short-period intensity was more significant than total rainfall.…”
Section: Introductionmentioning
confidence: 99%
“…The municipalities of Napoli and Pozzuoli (hereafter, PNMs) were chosen as the test area to validate the proposed methodology. It hosts about 3.183.465 people (ISTAT, 2017) and is exposed to volcanic (Lirer, Petrosino, Alberico, & Postiglione, 2001;Orsi, De Vita, & Di Vito, 1996), seismic (Esposito, Porfido, Luongo, & Petrazzuoli, 1992;Nunziata, 2004;Nunziata, Sacco, & Panza, 2011), flood (Esposito, Matano, & Scepi, 2018;Vennari, Parise, Santangelo, & Santo, 2016) (Figure 1). The deposits outcropping in the area were mainly emplaced by post-CI Campi Flegrei volcanic activity, and are made up of loose to lithified (tuffs) pyroclastic products and minor lava flows.…”
Section: Case Studymentioning
confidence: 99%
“…As reported by Esposito et al [61], many studies have underlined the valuable use of web news and social media for flood mapping [62], streamflow estimation [63,64], damage assessment [65], and flood prediction [66,67]. Crowdsourced data and Volunteered Geographic Information (VGI) have also been used to develop road damage maps, representing a fundamental tool in disaster response operations [68].…”
Section: Evaluation Of Flooding Impact Using Crowdsourced Datamentioning
confidence: 99%